Answer:
![\frac{(x-\frac{3}{7})(x+2)} {(x+\frac{2}{7})(x-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-%5Cfrac%7B3%7D%7B7%7D%29%28x%2B2%29%7D%20%7B%28x%2B%5Cfrac%7B2%7D%7B7%7D%29%28x-1%29%7D)
Explanation:
We have been given the expression![\frac{7x^2+11x-6}{7x^2-10x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B7x%5E2%2B11x-6%7D%7B7x%5E2-10x%2B3%7D)
given two expressions are quadratic
Using the formula to solve the quadratic equation is
![D=b^2-4ac](https://tex.z-dn.net/?f=D%3Db%5E2-4ac)
Now, to solve the equation for x where
![x=\frac{-b\pm\sqrt{D}} {2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7BD%7D%7D%20%7B2a%7D)
general quadratic equation is ![ax^2+bx+c](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc)
Comparing the numerator and denominator with general quadratic expression we will get
a=7,b=11,c=-6 in numerator
And a=7,b= -10,c=3 in denominator
And after substituting the values we will get
D=289 for numerator
and ![x=\frac{-11\pm17}{14} \\\\\Rightarrow\frac{3}{7} ,-2](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-11%5Cpm17%7D%7B14%7D%20%5C%5C%5C%5C%5CRightarrow%5Cfrac%7B3%7D%7B7%7D%20%2C-2)
And D=16 in denominator
and ![x=\frac{-(-10)\pm4}{14} \\\\\Rightarrow\frac{-2}{7} ,1](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-10%29%5Cpm4%7D%7B14%7D%20%5C%5C%5C%5C%5CRightarrow%5Cfrac%7B-2%7D%7B7%7D%20%2C1)
finally we will get ![\frac{(x-\frac{3}{7})(x+2)} {(x+\frac{2}{7})(x-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-%5Cfrac%7B3%7D%7B7%7D%29%28x%2B2%29%7D%20%7B%28x%2B%5Cfrac%7B2%7D%7B7%7D%29%28x-1%29%7D)